Fuzzy logic approach in power transformers management and decision making - Arshad, M.; Islam, Syed; Khaliq, A. (Institute of Electrical and Electronics Engineers Inc., 2014)
The degradation of insulation systems is a complex physical process, many parameters act at the same time thus making the interpretation extremely difficult. The insulation is very much responsive in transformer serving closer to design life. Strategic maintenance and operational procedures are best formulated where the condition of existing unit has been accurately assessed. To facilitate asset management and decision making, asset's condition assessment is vital using reliable, non-intrusive diagnostics and monitoring tools together with expert system. Transformer assessment can be carried out effectively by identifying and integrating its criticalities using fuzzy logic technique. In this research, asset management and decision making model has been developed using diagnostics and data interpretation techniques based on fuzzy logic approach. Enhance reliability could be achieved by integrating real time condition monitoring, maintenance, management activities and cost effective optimization techniques. This model facilitates effectively to address criticalities and allow better planning, maintenance approach as well as to predict the remnant life of the asset within a practical accuracy.